Controversial preservation of eye drops: the toxicity of benzalkonium chloride. (February 2023) - Hedengran, Anne; Kolko, Miriam
Abstract : Summary: Eye drops are a major cornerstone in the treatment of ophthalmic diseases, and adherence is crucial. Most eye drops are preserved with the surfactant benzalkonium chloride (BAK). Great controversy revolves around the use of BAK, as BAK has continuously been proven to be cytotoxic. In cell cultures, BAK-preserved eye drops cause increased cell death, and in patients, preservation with BAK causes more side effects and ocular surface damage. Side effects can negatively affect adherence and, with this, disease control. This is namely a problem in glaucoma patients. Glaucoma is irreversible, and a lack of disease control may lead to incurable blindness. The purposes of treating ophthalmic diseases are to secure good visual acuity, ocular comfort, and good quality of life for the patients. When administering, BAK-preserved eye drops ocular damage may be inflicted and these purposes are put at risk. Preservative-free and alternatively preserved eye drops are available, why there is no need for the use of BAK.